Building Renovation by Using Maximum Edge Distance Method - Priyadharshini, S.; Deepa, G. (Contemporary Mathematics, 2024)
In this competitive world, it is becoming more difficult to manipulate the entities for project managers and organizers to come up with successful project management strategies. Here, we introduce the Maximum Edge Distance (MED) methodology to determine the adequate solution for finding an intuitionistic fuzzy critical path (IFCP) for building renovation work. This methodology incorporates the use of intuitionistic fuzzy sets, allowing for the consideration of uncertainty and vagueness in the analysis. The Maximum Edge Distance approach involves assigning weights or distances to edges in the project network, optimizing the renovation work schedule by considering factors such as time, resource availability, and uncertainty. We used data from a construction company called Mega Star Technical, which specializes in renovations and building construction at Nigeria. This investigation will use the IFCP. Forward pass and backward pass computations are used for verification. MATLAB is used to manifest the simulation results. Finally, the results of this method demonstrate that the project is likely to be accomplish within the stated time range.